Creativity as a tool for new teaching-learning realities - Leopaci Benini, A. M. (2019)
This abstract presents a part of the bibliographic exploration part of a state-of-the-art presented in a Design PhD thesis. This PhD study seeks for innovation in design education through creative methodologies. It is a theoretical approach that serves as a basis for innovative practical applications in the teaching-learning process. The creativity is one of those approaches that has been the subject of all political and economic agendas in societies since the beginning of the 21st century, by its ability to solve problems through a holistic view. The methods and processes guided by creativity orientate the thoughts to reach results less obvious and more efficient. The Design Thinking methodology is one of those constructivist and exploratory approaches to creativity, a thought process that can intuitively design new realities, innovation, and problem-solving in an intuitive way. Before only used by designers and its schools, now this concept it is already introduced in educational explorations in the opposition to traditional education where the teacher owns the knowledge that passes the information to the students. This article presents through the methodology of a case study, the explorations of research teachers from different parts of the globe, in different areas of action, in order to understand how the teaching-learning processes and methodology’s using creativity have been applied to update. The objective is to understand how to stimulate the culture of creativity within education so that it can be transported to the textile industry, where a certain freedom of expression and action, necessary in creative environments, must be provided. However, this is little used when it comes specifically to the area where it is forced to work with fashion trends and fast consumption/discard products. This article presents, as a result, a reflection on the importance of creativity and its teaching within the academic environment and its subsequent use in business environments, in antithesis with the design associated with uncontrolled consumption, where the creation is usually done from an act mechanized and automatic.